Optimization of solenoid driver and controller for gaseous fuel high-pressure direct injector using model-based approach - Abdul Rahim, M. F.
Direct injection system for CNG fuel is a new development hence; the losses in solenoid drive direct fuel injector are not yet studied. The losses are suspected as the major cause for fluctuating injector mass flow rate which affected the engine torque stability due to the power losses. Solenoid drive internal losses are the major contribution to power losses. The key factor is non optimal driver current and voltage. Purpose of this study is to investigate the most influential type of power losses which affect the mass flow rate consistency and optimization of driver current and voltage to increase the controllability of the mass flow rate. Model-based optimization is the main method used to obtain the optimal setting for current and voltage of injector driver. In order to generate the experimental model by using offline system identification, cause-effect study is carried out by static and dynamic test. From the study, the primarily expected outcome are relationship between input and output variables of the injector flow, identification of significant losses based on the dynamic response analysis and optimum control of injector driver which will maximize the controllability of the injector flow rate. The results obtained from the study are important to increase the effectiveness of control strategies embedded in the development of dedicated driver and controller for the gaseous fuel direct injector.